A novel regulatory element responsible for high transcriptional expression of acerola GDP-d-mannose pyrophosphorylase gene*. Issue 6 (3rd June 2017) - Kondo, Takayuki; Fujikawa, Yukichi; Esaka, Muneharu
Abstract : GDP-d -mannose pyrophosphorylase (GMP) is one of the enzymes that highly expressed in acerola plants. A promoter assay suggests the presence of a new cis-element in the −1087 to −1083 bp sequence of the MgGMP promoter. Moreover, cis-elements, present in the −1080 to −600 bp sequence of the MgGMP promoter, function as enhancers of MgGMP expression.